Road-kills of the giant anteater in south-eastern Brazil: 10 years monitoring spatial and temporal determinants - Freitas, Carlos H. de [UNESP]; Justino, Carla S.; Setz, Eleonore Z. F. (Csiro Publishing, 2014)
Context. The giant anteater, Myrmecophaga tridactyla, is a large insectivorous mammal from Cerrado which is classified as vulnerable by the IUCN's red list. In spite of frequent giant anteater casualties, there continues to be a lack of published data on how road and landscape attributes affect road-kill rates - information that could prove useful in guiding mitigation measures.Aims. We seek to determine whether road and landscape attributes influence the incidence of road-kills of the giant anteater.Methods. From February 2002 to December 2012 (except for 2004), five roads in two regions in south-eastern Brazil were surveyed twice each month by car. We recorded temporal road-kill data for the giant anteater and related spatial road variables. These variables were also recorded at regular control sites every 2 km. We also took traffic volume data on stretches of the two roads to correlate with road-kills.Key results. Of the 45 anteater casualties recorded, there was a predominance of adult males. On roads MG-428 and SP-334, we found anteater road-kills were more common in the dry season, negatively correlated with traffic volume and related to the presence of native vegetation. Accordingly, road-kill sites tended to occur near the cerrado and grasslands and also appeared more frequently on some straight stretches of roadways. Although it was not shown to influence road-kill rates, topography data does point to regular overpass/underpass locations allowing population connectivity. Termitaria or ant nests were present at all road-kill sites, with 86% having signs of feeding.Conclusions. Native vegetation along roadways, together with straight road design, increases the probability of anteater road-kills by 40.1%.Implications. For mitigation, mowing and removing insect nests on roadsides, as well as roadside wildlife fencing in cerrado and grassland areas is suggested. Warning signs and radar to reduce vehicle speed are recommended for both human safety and anteater conservation. With regard to population connectivity, the absence of aggregated anteater road-kill data in this study meant that there were no particular crossing locations identified. However, the collected topography data do show places that could be used for roadway crossings. The measures indicated may apply to similar species and types of topography on other continents.
Keywords: Cerrado; Demography; Insectivores; Mitigation; Myrmecophaga tridactyla; Threat